1979
DOI: 10.3758/bf03326653
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal lesion effects on suppression of open-field activity in young and adult rats

Abstract: A total of 108 rats, 18-20, 30-32, or 100-130 days of age, received dorsomedial, orbital prefrontal, or sham lesions. After recovery, the subjects were assigned to one of three Pavlovian training conditions. Thirty-six subjects of each age level and surgical treatment received 2 days of 20 presentations of a 3D-sec, 3,OOO-Hz tone, during which inescapable shock of .5 sec duration was administered. The same number of subjects received the same treatment but without the shock, while the remaining subjects were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1982
1982
1984
1984

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…Anteromedial lesions of approximately the same size as those of the present study have been shown to impair a number of behaviors, such as spatial reversals (Divac, 1971), delayed alternation (Eichenbaum, Clegg, & Feeley, 1983), open-field activity (Brennan, 1979), and responding to reinforcement omission (McDonough & Manning, 1979). Thus, our negative results cannot be attributed simply to the small size of the lesions.…”
Section: Discussioncontrasting
confidence: 44%
“…Anteromedial lesions of approximately the same size as those of the present study have been shown to impair a number of behaviors, such as spatial reversals (Divac, 1971), delayed alternation (Eichenbaum, Clegg, & Feeley, 1983), open-field activity (Brennan, 1979), and responding to reinforcement omission (McDonough & Manning, 1979). Thus, our negative results cannot be attributed simply to the small size of the lesions.…”
Section: Discussioncontrasting
confidence: 44%